Kualitas Pelayanan Sekolah dan Kepuasan Siswa: Studi kuantitatif pada Siswa SMA/SMK di Indonesia Timur - Agnes Aryesam; Novihta Sampe; Mutiara Angelica Maseyra (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2020)
Abstract: The objective of this study is to analyze the quality of public school services and student satisfaction, with a focus on the population of students in public senior high schools (SMA) and vocational high schools (SMK) in Jayapura, Papua. This research employs a quantitative approach using a regression analysis model. The quality of school services was measured using the SERVQUAL (Service Quality) approach, which encompasses five primary dimensions commonly referred to as RATER: reliability, assurance, tangibles, empathy, and responsiveness. Meanwhile, student satisfaction was assessed using three main indicators, namely expectation conformity, intention to revisit, and willingness to recommend. The findings indicate that school service quality has a positive and significant effect on student satisfaction. This is evidenced by the t-value of 24.654 and a significance value of 0.000. The coefficient of determination (R²) is 0.612, indicating that school service quality contributes 61.2% to the variation in student satisfaction. Based on these findings, the study recommends the implementation of holistic service improvement strategies, including the enhancement of facilities and infrastructure, optimization of administrative services, transparency in academic information, responsiveness to student needs, and empathy in delivering services to students. Keywords: School Services; Student Satisfaction; SERVQUAL. Abstrak: Tujuan dari penelitian ini adalah menganalisis kualitas pelayanan sekolah negeri dan kepuasan siswa, dengan fokus pada populasi siswa di SMA/SMK Negeri di Jayapura, Papua. Penelitian ini menggunakan pendekatan kuantitatif dengan model analisis regresi. Kualitas Pelayanan sekolah diukur menggunakan pendekatan SERVQUAL (Service Quality) dengan lima dimensi utama yang dikenal sebagai RATER, yaitu: reliability, assurance, tangibles, empathy, dan responsiveness, sedangkan kepuasan siswa diukur dengan menggunakan tiga indikator utama yaitu kesesuaian harapan, minat berkunjung kembali dan kesediaan merekomendasikan. Hasil penelitian menunjukan bahwa bahwa kualitas pelayanan sekolah memiliki pengaruh positif dan signifikan terhadap kepuasan peserta didik Hal ini dibuktikan dengan nilai t hitung 24,654 dan nilai signifikansi 0,000. Nilai koefisien determinasi adalah sebesar 0,612 yang berarti besarnya sumbangan Kualitas Layanan Sekolah terhadap variabel Kepuasan peserta didik adalah 61,2%. Hasil penelitian ini merekomendasikan penerapan strategi peningkatan layanan secara holistik, meliputi perbaikan sarana dan prasarana, optimalisasi layanan administratif, keterbukaan informasi akademik, ketanggapan terhadap kebutuhan siswa, serta perlunya empati dalam melayani siswa. Kata kunci: Layanan Pedidikan; Kepuasan Siswa; SERVQUAL.